The Dialectic of The National Criminal Code and The Living Law: A Philosophical Approach to Contemporary Criminal Law - Kusumawardhani, Dwinanda Linchia Levi Heningdyah Nikolas (Postgraduate Program in Law, Universitas Pattimura, 2025)
Introduction: This study examines the dialectical relationship between the National Criminal Code and the living law through the contemporary criminal law philosophy approach. The existence of the Criminal Code as a formal legal product of the state is often in tension with the customary law system and the values that live in pluralistic Indonesian society.Purposes of the Research: This research aims to analyze the patterns of interaction, contradictions, and potential harmonization between the two legal systems.Methods of the Research: Using juridical-philosophical research methods and legal hermeneutic approaches, this study explores the ontological, epistemological, and axiological dimensions of the dialectic.Results Main Findings of the Research: The results of the study show that despite paradigmatic tensions, the two legal systems can run in a complementary manner through an integrated legal pluralism recognition mechanism. This research offers a new conceptual framework in understanding the nature of criminal law that is responsive to social change but still upholds legal certainty. The findings of the research have implications for the urgency of reformulating the Criminal Code that accommodates the living law while maintaining the fundamental principles of modern criminal law, especially legality, proportionality, and protection of human rights. This dialectical approach is an important foundation for the development of a contextual, fair, and sustainable Indonesian criminal law system.